Environmental Impact Reduction Analysis on PT XYZ Asphalt Production using Life Cycle Assessment (LCA) and Analytical Hierarchy Process Method (AHP) - Putri Tandriani Sundana; Udisubakti Ciptomulyono (Journal of Social Research, 2026)
Research was conducted on the environmental impact analysis of the asphalt production process at PT XYZ, with the aim of identifying and determining the magnitude of the environmental impact of asphalt production. It also aimed to identify alternative strategies to reduce the environmental impact of asphalt production. The data used consists of primary and secondary data. The analysis method to determine the magnitude of the environmental impact of asphalt production was carried out using the LCA (Life Cycle Assessment) method with the ReCiPe 2026 Midpoint and Endpoint methods. Meanwhile, the analysis of the environmental impact reduction program was carried out using the AHP (Analytical Hierarchy Process) method with Expert Choice 11. The production process of 1 metric ton of asphalt distributed at PT XYZ produces endpoint impacts including human health of 63,062.033 Pt, ecosystem of 8,440.988 Pt, and resources of 72.541 Pt. Meanwhile, the most dominant midpoint impact is global warming, with a characterization value of 5,360,044.8 kg CO? eq. The unit with the highest impact contribution is the storage unit, due to its high electricity consumption. Uncertainty analysis or Monte Carlo simulation was performed on the data using the dataset. Based on the uncertainty analysis conducted on the grave, it is known that 1 metric ton of distributed asphalt produces an ecosystem environmental impact of between 171,651.00 and 417,824.27 Pt, human health between 2,181,108.80 and 3,917,701.50 Pt, and resource between 117,301.19 and 243,365.28 Pt. The environmental program priority selected through the AHP method is the “Automation of Heater Switch On/Off Shutdown with Temperature Sensor” program. This program can reduce the midpoint global warming impact by 16.7%, the endpoint human health impact by 16.7%, and the ecosystem impact by 16.7%.